Sub-diffraction imaging via surface plasmon decompression - Salandrino, Alessandro; Hu Cang; Yuan Wang; Xiang Zhang (2014 Conference on Lasers and Electro-Optics (CLEO) - Laser Science to Photonic Applications, 2014)
We theoretically propose a novel scheme for sub-diffraction imaging based on a process of adiabatic decompression of the local wavelength of a surface plasmon polariton supported by two adjoining curved metal surfaces.